Novel insights in the diagnosis of Cushing's syndrome. - Alexandraki, K; Grossman, AB (2010)
Cushing's syndrome (CS) results from sustained pathologic hypercortisolism. Increased identification of cyclical CS and the similarities between the metabolic syndrome and mild CS has resulted in an increased prevalence of CS, necessitating more accurate diagnostic tests to screen and diagnose CS in its earliest stages. Many studies have examined the utility of resistance to steroid feedback by the dexamethasone suppression tests and increases in secretion assessing 24-hour urinary free cortisol; however, the most sensitive indicator is the loss of circadian rhythmicity. Therefore, midnight sleeping cortisol is undoubtedly an extremely sensitive indicator of CS but impractical for screening purposes. In this situation assessment late-night salivary cortisol (NSC) is being increasingly investigated as a simple and convenient outpatient procedure. Salivary cortisol has also been used in stimulation or suppression tests because of the detection of rapid changes in cortisol concentration. This paper discusses the effectiveness of SC as a putative accurate, stress-free, and non-invasive sampling procedure. Some studies have shown no difference between tests while others demonstrated a higher sensitivity of SC, while the combination of tests seems to increase their diagnostic value. However, the different assays used for SC estimation and the variable types of control groups in the published studies render a comparison of studies difficult. In conclusion, NSC measurement is increasingly being used as a first-line test for CS, but we recommend that local centres establish their own normative ranges, and there is still a place for the more traditional tests to confirm the diagnosis.